A Low Voltage Single Phase Online Uninterruptible Power Supply System Based on APFC and Fuzzy PID Algorithm - Xu, Shengxian; Li, Chen; Wang, Yuru; Li, Baoying (IEEE access, 2021)
The Uninterruptible Power Supply (UPS) is a kind of power supply with electric energy storage, but most UPS systems bring harmonic pollution to the grid, and the power factor is inaccurate in the boost circuit, the output voltage is unstable. Therefore, an active power factor correction circuit (APFC) based on the current and voltage double closed-loop structure is designed in the boost circuit; besides, the fuzzy PID control algorithm is also proposed in the inverter circuit. The effectiveness of the proposed method can be verified by the computer simulation and real experiments, and there are four main results as follows. Firstly, the actual power factor of the UPS system can reach more than 0.996 with APFC correction circuit; then, the UPS system has the strong robustness and the shorter response time; in addition, the voltage regulation rate of the system remains at 0.083% and the load regulation rate is around 0.056%. Finally, the designed UPS system can provide the stable 36V ± 0.2V (50 ± 0.2Hz) AC power.